Optimizing Key Performance Indicators and Lifecycle Stages in the Iraq Construction Industry: A Systematic Review and Generic Framework Development - Saber, Avan Kanbi (Eastern Mediterranean University, 2023)
The objective of this study is to propose a generic framework, for constructing energy efficient high rise buildings in Iraq. This framework aims to address challenges and achieve long term sustainability goals. The development of this framework is based on an in depth analysis of 69 papers. Incorporates various sustainable indicators throughout different stages of the construction process. In the design phase the framework integrates elements such as incorporating energy using materials in construction implementing water conserving landscaping, smart irrigation systems and designing energy efficient ventilation systems. As the construction phase begins the framework also considers energy storage solutions like batteries and building automation systems to optimize energy usage and enhance efficiency. During the utilization phase several strategies can be employed to promote sustainability and improve efficiency. These strategies include implementing energy efficiency upgrades obtaining building certifications, recycling and reusing water resources minimizing waste generation through source reduction measures providing on site waste management facilities along, with segregation and sorting mechanisms conducting regular maintenance activities employing lighting control measures based on occupancy feedback and monitoring systems. By adopting these practices during the phase of high rise buildings life cycle can effectively contribute towards achieving goals related to energy efficiency improvement, emissions reduction, water conservation efforts while enhancing environmental quality. During the phase of a products life cycle the framework combines circular economy initiatives. These initiatives aim to promote waste management and minimize impact. The proposed generic framework holds significance as it enables progress in sustainability, within Iraqs high rise building construction sector. This contribution would be valuable in efforts to combat climate change and foster sustainable development. However successful implementation requires overcoming challenges such, as regulatory constraints, financial considerations, raising awareness and access to sustainable technologies. Keywords: energy efficiency, building energy, high rise building, energy performance, key performance indicators, construction life cycle

Bu çalışmanın amacı, Irak'ta enerji verimli yüksek katlı binaların inşasını öneren genel bir çerçeve sunmaktır. Bu çerçeve, zorlukları ele almayı ve uzun vadeli sürdürülebilirlik hedeflerine ulaşmayı amaçlamaktadır. Bu çerçevenin geliştirilmesi, 69 makalenin derinlemesine analizine dayanmaktadır ve inşaat sürecinin farklı aşamalarında çeşitli sürdürülebilir göstergeleri içermektedir. Tasarım aşamasında, çerçeve enerji kullanımını içeren malzemeleri inşaata dahil etme, su tasarruflu peyzaj düzenlemesi uygulama, akıllı sulama sistemlerini kullanma ve enerji verimli havalandırma sistemlerini tasarlama gibi unsurları sorunsuz bir şekilde entegre etmektedir. İnşaat aşaması başladığında, çerçeve aynı zamanda enerji depolama çözümlerini, bataryaları ve bina otomasyon sistemlerini enerji kullanımını optimize etmek ve verimliliği artırmak amacıyla dikkate almaktadır. Kullanım aşamasında, sürdürülebilirliği teşvik etmek ve verimliliği artırmak için bir dizi strateji kullanılabilir. Bu stratejiler, enerji verimliliğini artırmayı, bina sertifikalarını elde etmeyi, su kaynaklarını geri dönüştürmeyi ve yeniden kullanmayı, kaynak azaltma önlemleri ile atık oluşturmayı en aza indirmeyi, ayrıştırma ve sıralama mekanizmalarıyla birlikte yerinde atık yönetimi tesisleri sağlamayı, düzenli bakım faaliyetlerini yürütmeyi, işgal geri bildirimine dayalı aydınlatma kontrol önlemlerini içermektedir. Yüksek katlı binaların yaşam döngüsü aşamasında, bu uygulamaları benimseyerek enerji verimliliğini iyileştirme, emisyon azaltma, su koruma çabalarını güçlendirme ve çevresel kaliteyi artırma gibi hedeflere etkili bir şekilde katkı sağlamak mümkün olabilir. Ürün yaşam döngüsü aşamasında, çerçeve dairesel ekonomi girişimlerini birleştirir. Bu girişimler, atık yönetimini teşvik etmeyi ve olumsuz çevresel etkileri en aza indirmeyi amaçlar. Önerilen genel çerçeve, Irak'ın yüksek katlı bina inşaat sektöründe sürdürülebilirlik alanında ilerlemeyi mümkün kılarak önemli bir rol üstlenmektedir. Bu katkı, iklim değişikliğiyle mücadele ve sürdürülebilir kalkınmayı destekleme çabalarında değerli bir rol oynayacaktır. Ancak başarılı uygulama için düzenleyici kısıtlamalar, mali düşünceler, farkındalığı artırma ve sürdürülebilir teknolojilere erişim gibi zorlukların üstesinden gelinmesi gerekmektedir. Anahtar Kelimeler: enerji verimliliği, bina enerjisi, yüksek bina, enerji performansı, temel performans göstergeleri, inşaat yaşam döngüsü
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2023. Co-Supervisor: Dr. Mehmet Sakin and Supervisor: Assoc. Prof. Dr. Tolga Çelik
Keywords: Thesis Tez; Civil Engineering Department; Buildings--Energy conservation--Iraq; Buildings--Environmental aspects--Sustainable buildings; Architecture and energy conservation--Iraq; Green technology; Energy efficiency; building energy; high rise building; energy performance; key performance indicators; construction life cycle